Analysis of the Implementation of BPJS Employment Policy in Improving the Welfare of Informal Workers in Medan City - Simbolon, Geby Monica; Helsin Maria S; Sitepu, Natanael; Situmeang, Joudi Cristian (MSJ : Majority Science Journal, 2026)
Every worker has the right to occupational safety protection, both formal and informal workers. The absence of social security can weaken worker protection and impact their performance and welfare. In Medan City, the level of informal worker participation in the BPJS Ketenagakerjaan program remains low due to a lack of information, economic constraints, and less than optimal socialization. BPJS Ketenagakerjaan, as a public legal entity responsible to the president, has a mandate to administer the Work Accident Insurance (JKK), Death Insurance (JKM), Old Age Insurance (JHT), and Pension Insurance (JP) programs for all workers, including migrant workers who have worked for at least six months. The low participation of informal workers indicates that worker welfare in Indonesia has not been fully met. This study aims to analyze the factors causing low BPJS Ketenagakerjaan participation among informal workers in Medan City and assess BPJS Ketenagakerjaan's efforts to increase their participation. A descriptive qualitative approach was used through in-depth interviews, field observations, and document studies. The analysis was conducted using the George C. Edwards III policy implementation model, which emphasizes aspects of communication, resources, implementer disposition, and bureaucratic structure. Preliminary results show that despite efforts to increase socialization and expand participation, obstacles such as affordability of contributions, lack of understanding of benefits, and inconsistent implementation in the field remain major challenges.